Peripherally Inserted Central Catheter Fracture in a Preterm Neonate—Case Report. Issue 2 (June 2023) - Mukherjee, Devdeep; Das, Saurabhi; Bhattacharjya, Sudipto; Nayak, Hemant Kumar
Peripherally inserted central catheters (PICC) are commonly used in the neonatal intensive care unit. They help in administering fluids, nutrition, and antibiotics. They have a lower risk for injury, infection, and thrombosis compared to central venous catheters. PICC fracture in a neonate has been rarely documented. We present a pre term neonate who had a PICC fracture remnant in the right atrium which was diagnosed following a contrast x ray and echocardiography. The PICC was removed percutaneously by our intervention pediatric cardiologist. All central venous access lines should be carefully monitored in the neonatal intensive care unit for risk of complications.